Lama menjadi Kader dan Pengetahuan Kader dalam Pencegahan Stunting menggunakan Video Animasi - Titik Sapartinah; Titi Mursiti; Heny Rosiana (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
Stunting is a condition of stunted growth in children under five years of age (toddlers) resulting from chronic malnutrition and recurrent infections, particularly during the